Representasi Bahasa Figuratif dan Citraan dalam Novel Anjing Mengeong dan Kucing Menggonggong: Kajian Stilistika: Figurative Language Representation and Imagery in the Novel Anjing Mengeong dan Kucing Menggongong: A Stylistic Study - Fardeni, Haekal; Maulina, Intan (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study analyzes the use of figurative language and imagery in the novel Anjing Mengeong dan Kucing Menggonggong by Eka Kurniawan using a stylistic approach. The metaphorical language discussed includes metaphor, simile, personification, hyperbole, and litotes. Meanwhile, the imagery analyzed includes visual, auditory, tactile, gustatory, and olfactory imagery. The analysis results show that the use of figurative language and imagery in this novel is very effective in strengthening the narrative, creating an atmosphere, and describing the characters and setting of the story in a more vivid and immersive way. The use of figurative language helps enhance the aesthetic beauty of the text and conveys meaning indirectly. Imagery enhances the reading experience by arousing the reader's senses through detailed and vivid descriptions. This study also shows that Eka Kurniawan's writing style uniquely combines aesthetic elements and meaning. Figurative language and imagery are used not only as literary ornaments but also as a means to convey complex social, psychological, and cultural messages. By observing how these language styles are used in the novel, readers are invited to better understand the narrative's depth and the characters' inner conflicts. Hopefully, These findings can contribute to literature learning at the high school level, especially in increasing students' appreciation of the richness of language in modern Indonesian literary works.